Sumbangan Shah Waliyullah al-Dihlawi dalam Perkembangan Intelektual Islam di Malaysia: Beberapa Perkembangan Mutakhir: Shah Waliyullah al-Dihlawi’s Contribution to Islamic Intellectual Development in Malaysia: Some Recent Developments - Narmi, Akalily; Abdul Rani, Mohd. Zariat; Kamarudin, Kamariah; Hajimaming@Toklubok, Pabiyah (Journal of Al-Tamaddun, 2022)
In the study of civilization, the intellectual achievement of a nation becomes an important aspect that is given great attention. The civilization of a nation is usually formed from interaction with other nations, especially through the influence of intellectual achievement. In this context, this study focuses on the influence of Shah Waliyullah al-Dihlawi in Malaysia. Al-Dihlawi was a Muslim Indian-born scholar in the 18th century AD who made great contributions in the Islamic scientific tradition to this day. Existing research corpus on his contribution in Malaysia is found to comprise of studies which tend to be very specific in their focus, scope and period. This tendency invites for a more comprehensive study, especially which takes into account recent developments. This study, therefore, aims to chronologically discuss the influence of al-Dihlawi’s ideas in Malaysia, including their most recent developments. The study adopts a qualitative methodology, specifically using library research and interviews. The study finds that there are some recent developments in relation to the influence of Dihlawi’s ideas in Malaysia, particularly in the field of Malay literature. This refers to the application of Taklif according to al-Dihlawi‘s explication in Persuratan Baru (officially translated as “Genuine Literature”), a notion by Mohd. Affandi Hassan which has been applied as a framework for analysing Malay literary texts. This application has formed a distinct academic corpus on al-Dihlawi’s thought in Malay literature.